ANALISIS RANTAI PASOK PADA KOMODITAS KOPRA DI DESA LOWIAN KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - Taula, Vinni S.; Pakasi, Caroline Betsi Diana; Baroleh, Jenny (Sam Ratulangi University, 2022)
The study aims to identify supply chains based on product flow, information flow, financial flow and analyze the level of marketing efficiency in the copra commodity supply chain. This research was carried out for three months, from August to October 2021, which took place in Lowian Village, Maesaan District, South Minahasa Regency. This study uses primary data and secondary data. The population in this study were all coconut farmers and copra collectors. Sampling using a simple random sampling method (simple random sampling) obtained 50 farmers from a population of 248 farmers and 3 traders collectors. The results showed that the supply chain in Lowian Village was based on product flow from upstream to downstream starting from copra farmers, collectors, and copra processing factories. The flow of information flows from two directions, namely the first direction the factory provides information to traders about the quality and price of copra needed then traders provide price information to farmers, the second direction is farmers provide information to traders about the quality of copra sold then traders will inform the factory about the volume marketing of copra to be sold. As for the financial flows from downstream to upstream, starting from factories that buy copra from collecting traders via bank transfer, then collecting traders buy copra from farmers with a cash payment system. The level of marketing efficiency in the copra supply chain seen from the total marketing margin, marketing costs and profits has been efficient.